Multimedia Input and Bilingual Children’s Language Learning - Sun, He; Yin, Bin (Frontiers in Psychology, 2020)
The current study seeks to explore the impact of multimedia input at home on bilingual children’s language outcomes. Two hundred and two Singaporean English-Mandarin kindergarteners’ multimedia experience (i.e., the resources and the amount of multimedia input) and conventional language exposure (e.g., language use with family members) were investigated with a parental questionnaire. A series of English and Mandarin tests were conducted to assess children’s proficiency (i.e., in receptive vocabulary, receptive grammar, verbal fluency) by standardized measures. Results demonstrated that the diversity of multimedia input is more important than the amount of multimedia input in promoting children’s Mandarin language maintenance, while controlling for children’s conventional language exposure, SES, and language aptitude. The number of multimedia sources is significantly and positively related to children’s general Mandarin proficiency. In contrast, English multimedia exposure at home exerts little impact on children’s general English proficiency. The findings indicate the unique contribution of multimedia diversity to children’s early heritage language maintenance. The strong social relevance of the study is discussed at the end of the paper.